EFFECT OF PROFESSIONAL DEVELOPMENT OPPORTUNITIES ON JOB SATISFACTION OF WOMEN FACULTY IN MADURAI DISTRICT - R. Lavanya; S. Chitra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the impact of professional development opportunities on the job satisfaction levels of women faculty in higher education institutions. The research explores how access to training, workshops, seminars, and career advancement programs influence job motivation, academic productivity, and institutional loyalty among female educators. A mixed-method approach was adopted using survey questionnaires and interviews with women faculty members across selected universities. The findings reveal a significant positive correlation between professional development initiatives and job satisfaction, emphasizing the importance of institutional support in faculty growth and retention.